2004
DOI: 10.1002/qua.20238
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio studies of stepped {100} surfaces of KDP crystals

Abstract: Potassium dihydrogen phosphate (KH 2 PO 4 , KDP) crystals have important uses in laser components and are grown in large scale for that purpose. The need for habit control has led to interest in the step-pinning mechanisms that cause growth inhibition of the {100} face. Model systems representing five stepped KDP {100} surfaces are prepared and studied using ab initio quantum methods. Results of Hartree-Fock and density functional theory plane-wave calculations are presented, including estimated energies of io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…We have studied five possible steps on the {100} face of KDP (see Figure 4) using ab initio quantum methods, and we have presented energetic data which may be useful in theoretical modeling of KDP crystal growth [18,19]. We have presented estimated surface removal energies for the {100} and {101} faces, as well, and we have confirmed that the K + -bounded {101} face has a higher surface removal energy than the H2PO4 --bounded {101} face.…”
Section: Molecular Modeling Of Aluminum Incorporation In the Kdp Latticementioning
confidence: 70%
“…We have studied five possible steps on the {100} face of KDP (see Figure 4) using ab initio quantum methods, and we have presented energetic data which may be useful in theoretical modeling of KDP crystal growth [18,19]. We have presented estimated surface removal energies for the {100} and {101} faces, as well, and we have confirmed that the K + -bounded {101} face has a higher surface removal energy than the H2PO4 --bounded {101} face.…”
Section: Molecular Modeling Of Aluminum Incorporation In the Kdp Latticementioning
confidence: 70%
“…The combined effect of the above two mechanisms leads to a strong transverse growth arrest of prismatic faces, yet a high-speed growth of the pyramidal face. In the following, we present density functional theoretical (DFT) analysis to support this molecular orientation based self-shielding and self-channeling hypothesis. We first calculate surface adsorption energy of a molecule on the (100) face/surface of a KDP unit cell, revealing a strong molecular-orientation selectivity in the surface-adsorption process.…”
Section: Resultsmentioning
confidence: 87%
“…We refer to the termination where the protons of the step-edge phosphates point parallel to the surface as A (Figure b) and to the termination where the protons point normal to the surface as B (Figure c). On the {001}-facing step, one termination is the most energetically stable (Figure d) 3 Atomic structures of the KDP surface.…”
Section: Methodsmentioning
confidence: 99%